Prevalence of Elevated Blood Pressure and Risk Factors Among Men and Women in Six Regions of Ethiopia. (14th June 2022) - Hemler, Elena; Bromage, Sabri; Passarelli, Simone; Tadesse, Amare Worku; Andersen, Christopher; Sudfeld, Christopher; Berhane, Yemane; Fawzi, Wafaie; Danaei, Goodarz
Abstract: Objectives: Hypertension is a growing problem in Ethiopia; large representative surveys are needed to elucidate the burden of raised blood pressure and regional differences. Methods: A population-based cross-sectional survey including 2, 520 women and 1, 054 men aged 15–49 years was carried out in six regions of Ethiopia (Addis Ababa, Afar, Amhara, Oromia, Southern Nations Nationalities and Peoples [SNNP], and Tigray). All participants completed a household questionnaire, a food frequency questionnaire (FFQ) and underwent blood pressure and height and weight measurements. Population-weighted prevalences were calculated for prehypertension (defined as systolic blood pressure 120–139 mmHg or diastolic blood pressure 80–89 mmHg) and elevated blood pressure (defined as systolic blood pressure ≥ 140 mmHg or diastolic blood pressure ≥ 90 mmHg). Multivariable-adjusted associations of risk factors with systolic blood pressure were estimated using survey-weighted linear regression models. Results: Across the six regions, 41% of participants had prehypertension (39% among women and 47% among men) and 17% had elevated blood pressure (17% among women and 16% among men). Regional prevalence of prehypertension was lowest in Tigray (31%) and Afar (30%) and highest in SNNP (44%) and Amhara (43%). Prevalence of elevated blood pressure was lowest in Tigray (9%) and Afar (8%) and highest in SNNP (19%), Oromia (19%), and Addis Ababa (18%). The Global Diet Quality Score Positive Submetric (GDQS+) reflecting higher intake of 16 healthy food groups was inversely associated with systolic blood pressure (Adjusted mean difference [AMD] −0.35 mmHg; 95% Confidence Interval [CI]: −0.64, −0.05). Body Mass Index (BMI) was positively associated with systolic blood pressure (AMD 0.68 mmHg; 95% CI: 0.34, 1.01). Among men, drinking alcohol was associated with higher systolic blood pressure (AMD 3.14 mmHg; 95% CI: 1.25, 5.03). Conclusions: Prevalence of prehypertension and elevated blood pressure among adults aged 15–49 in six regions of Ethiopia is high, with important regional differences. Diet quality, BMI and alcohol use among men are important modifiable risk factors that interventions in Ethiopia could target to lower risk of prehypertension and elevated blood pressure. Funding Sources: This work was supported by the Bill and Melinda Gates Foundation Grant OPP1179606.